Corporate trust language and its impact on information transparency in an emerging market - Rajabalizadeh, Javad; Rezaee, Zabihollah (The Spanish Accounting Academics Association (ASEPUC), 2026)
Purpose
This study examines whether the use of trust-related language in the management discussion and analysis (MD&A) sections of corporate reports influences perceptions of information transparency in Iranian firms.
Design/methodology/approach
Using 1,897 firm-year observations from Iranian listed firms between 2011 and 2023, trust language (TRUSTTL) is measured by identifying and counting trust-related words in MD&A reports based on an expanded lexicon containing 98 Persian-specific keywords. Information transparency is proxied by deviations in firm value (DEVIATION).
Findings
The results show a significant negative relationship between TRUSTTL and DEVIATION, suggesting that greater use of trust-related language is associated with improved information transparency. These findings support the incremental information perspective, indicating that trust language can reduce information asymmetry between firms and investors. However, the positive effect weakens when MD&A disclosures exhibit excessive complexity or overly optimistic tone, which may undermine credibility and reduce stakeholder trust.
Originality/value
This study extends the corporate disclosure literature by examining the role of trust-related language in MD&A reports within a non-English and emerging market context. By developing a Persian-specific trust lexicon and empirically testing its effects on transparency, the research provides new insights into how linguistic features influence the informativeness of corporate communication.